KONSEP STANDAR PROSES DALAM PEMBELAJARAN MATEMATIKA - Nasution, Mariam (IAIN PADANGSIDIMPUAN, 2018)
In the process of mathematics learning a teacher must be able to create a meaningful learning process. A good learning process will be able to achieve the goal of learning to the fullest. Teacher learning process should be able to bring the creativity of students, skills, liveliness and can solve problems. Mathematics Learning formulated by the National Council of Teachers of Mathematics or NCTM outlines that students must learn mathematics through understanding and actively build new knowledge from experience and knowledge that has been previously owned The standard in the process of learning mathematics are: 1) Understanding the concept of mathematics, 2) Mathematical reasoning, 3) mathematical communication, 4) Mathematical connection, 5) Mathematical problem solving. The five standard processes should not be viewed as something separate from the standard contents in the mathematics curriculum. The five standard processes direct the method-methods or processes to do all of mathematics, therefore, they must be seen as integral components with learning and teaching. The process standard refers to the mathematical process through which the student acquires and uses mathematical knowledge to derive the learning objectives set at the school level.